Direction splitting of ϕ-functions in exponential integrators for d-dimensional problems in Kronecker form - Caliari, Marco; Cassini, Fabio (Journal of Approximation Software, 2024)
In this manuscript, we propose an efficient, practical and easy-to-implement way to approximate actions of ϕ-functions for matrices with d-dimensional Kronecker sum structure in the context of exponential integrators up to second order. The method is based on a direction splitting of the involved matrix functions, which lets us exploit the highly efficient level 3 BLAS for the actual computation of the required actions in a µ-mode fashion. The approach has been successfully tested on two- and three-dimensional problems with various exponential integrators, resulting in a consistent speedup with respect to a technique designed to approximate actions of ϕ-functions for Kronecker sums.